1990
DOI: 10.1128/iai.58.6.1879-1885.1990
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Salmonella typhimurium genes required for invasion is regulated by changes in DNA supercoiling

Abstract: The ability to enter intestinal epithelial cells is an essential virulence factor of salmonellae. We have previously cloned a group of genes (invA, B, C, and D) that allow S. typhimurium to penetrate tissue culture cells (J. E. Galan and R. Curtiss III, Proc. Natl. Acad. Sci. USA 86:6383-6387, 1989). Transcriptional and translational cat and phoA fusions to invA (the proximal gene in the invABC operon) were constructed, and their expression was studied by measuring the levels of alkaline phosphatase or chloram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
119
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(126 citation statements)
references
References 59 publications
(60 reference statements)
5
119
2
Order By: Relevance
“…Concomitantly, development of mutations conferring resistance to fluoroquinolones as a result of heavy exposure may have occurred, either in parallel or following an assortive recombination of chromosomal regions encoding resistance and virulence genes [34]. Alternatively, Preisler et al [35] have reported that the gyrA mutations that confer fluoroquinolone resistance also affect supercoiling of DNA, which has been shown to affect virulence gene expression [36][37][38]. Other studies have revealed that inhibition of DNA gyrase with antibiotics (i.e., novobiocin) specifically affects transcription of type III virulence genes [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitantly, development of mutations conferring resistance to fluoroquinolones as a result of heavy exposure may have occurred, either in parallel or following an assortive recombination of chromosomal regions encoding resistance and virulence genes [34]. Alternatively, Preisler et al [35] have reported that the gyrA mutations that confer fluoroquinolone resistance also affect supercoiling of DNA, which has been shown to affect virulence gene expression [36][37][38]. Other studies have revealed that inhibition of DNA gyrase with antibiotics (i.e., novobiocin) specifically affects transcription of type III virulence genes [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, Preisler et al [35] have reported that the gyrA mutations that confer fluoroquinolone resistance also affect supercoiling of DNA, which has been shown to affect virulence gene expression [36][37][38]. Other studies have revealed that inhibition of DNA gyrase with antibiotics (i.e., novobiocin) specifically affects transcription of type III virulence genes [36][37][38][39]. Thus, the potential for fluoroquinolone resistance to affect TTSS gene expression as a result of changes in DNA supercoiling has already been demonstrated in other bacterial species [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The transmigration of M cells by Salmonella is an active process which requires the induction of genes encoded by so-called pathogenicity islands. Such genes are strongly induced when Salmonella are grown under anaerobic conditions and high salt [15,16]. To take this into consideration, cultures were always grown without aeration.…”
Section: In£uence Of Growth Conditions On Immunisation E¤ciencymentioning
confidence: 99%
“…We designed a thrombin-inhibiting aptamer, to which we attached 36-, 27-or 18-mer complementary sequences of target DNAs at its 5 0 or 3 0 end. We used three different DNA sequences as the target DNAs: a part of the Salmonella invA gene (nucleotide positions 426 to 452) was used for the AES invA series (Galan et al 1990), a part of the SARS coronavirus genomic antisense sequence (genome location 15348 to 15383) (Rota et al 2003;Marra et al 2003) for the AES SARS 1 series and a part of the SARS coronavirus genomic sequence (genome location 15561 to 15596) for the AES SARS 2 series. The 36-, 27-and 18-mer DNA sequences were used as the target DNAs, and these complementary strands were added to the thrombin-inhibiting aptamer at its 5 0 or 3 0 end.…”
Section: Design Of the Aptameric Enzyme Subunitmentioning
confidence: 99%